(untitled) (World Bulletin of Management and Law, 2024)
Ever since a person perceives himself as a conscious being, it has an existential impact on his way of life, income and activity. He puts his created wealth through the scales of intelligence and the test of time. In this way, it leaves a social-geographical, historical-cultural and moral environment and values necessary for future generations. The value of the Uzbek people to such cultural heritage is the neighborhood institution. It is worth noting that the institution that took a lifelong place in the lifestyle of the Uzbek people is the neighborhood